Nutritional, physico-chemical and health-promoting properties of selected watermelon (citrullus lanatus (thunb.) matsum. & Nakai) varieties - Sarmin, Sabeetha (2015)
Watermelon (Citrullus lanatus) is a popular fruit among Malaysian. Red-fleshed seedless, red-fleshed seeded and yellow-fleshed watermelon are mostly selected as a dessert and available throughout the year in local markets. However, studies that look into the health properties of watermelon are still lacking. Therefore, this study determined the nutritional, the physico-chemical and the health-promoting properties of different types of watermelons. The results obtained that red-fleshed seedless watermelon contained 89.6 ± 4.3% moisture, while red-fleshed seeded and yellow-fleshed watermelon had 87.5 ± 2.6 % and 87 ± 2.7 %, respectively. Furthermore, no significant difference was detected for most nutritional and physico-chemical analyses between the samples. However, there were significant differences for colour value (L*, a* and b*) and amount of sucrose. Yellow-fleshed watermelon has the highest values for L* (49.99 ± 6.92), followed by red-fleshed seedless watermelon (43.44 ± 3.48) and red-fleshed seeded watermelon (38.2 ± 5.09). Yellowfleshed watermelon also has the lowest value of a* (5.77 ± 2.00) and the highest value of b* (32.59 ± 8.77). Types of sugars present in red-fleshed seedless, red-fleshed seeded and yellow-fleshed watermelon were glucose,fructose and sucrose. The amount of total sugar was 95 ± 25.2 mg/g for redfleshed seedless, 113.8 ± 31.6 mg/g for red-fleshed seeded and 103.1 ± 27.7 mg/g for yellow-fleshed watermelon. There was a positive and strong correlation between total soluble solid and total sugar (r2 = 0.75). Meanwhile, the antioxidant contents among these watermelons were evaluated using total phenolic content (TPC), 2,2-diphenyl-1-picrylhydrazyl radical scavenging (DPPH), Trolox equivalent antioxidant capacity (TEAC) and ß-carotene bleaching. The red-fleshed seedless watermelon had the highest amount of phenolic content (21.58 ± 2.9 mg GAE/100g edible portion) and ß-carotene bleaching activity (57.29 ± 3.53%) while red-fleshed seeded watermelon had the highest amount of antioxidant capacity (1.17 ± 0.43 μmol TE/g edible portion) and percentage radical scavenging activity of DPPH (21.14 ± 2.03) compared to yellow-fleshed watermelon. Furthermore, the highest correlation between the red-fleshed and yellow-fleshed watermelon showed a positive correlation (r2 = 0.877) with a significant difference (p<0.01) observed between total phenolic content and ß-carotene bleaching activity, while the lowest correlation (r2 = 0.344) had no significant difference for total phenolic content with antioxidant capacity. The glycemic index was conducted on 14 healthy subjects who that consumed 25 g of available carbohydrate portions of glucose (standard food) and four test foods (red-fleshed seedless watermelon, redfleshed seeded watermelon and yellow-fleshed watermelon, as well as a glass of red-fleshed seedless watermelon juice) in random order after an overnight fast. Red-fleshed seedless watermelon was usually processed as juice than red-fleshed seeded and yellow-fleshed watermelon. Glucose was measured at 0, 15, 30, 45, 60, 90 and 120 min after intake of the test foods. Incremental areas under the curve were calculated, whereas the glycemic index was determined by expressing the area under the curve after the test foods, as a percentage of the mean area under the curve after consuming standard food,was carried out. The results showed that the area under the curve for a portion of red-fleshed seedless was 98.17 ± 6.39, red-fleshed seeded (94.10 ± 7.45),yellow-fleshed (92.95 ± 8.73), and a juice of red-fleshed seedless (98.89 ±6.38) did not have any significant difference (p<0.05). It means the glycemic index among samples did not significant differ statistically. The glycemic index of a portion fruit and the juice of red-fleshed seedless watermelon was 51, while red-fleshed seeded watermelon was 48 and yellow-fleshed watermelon was 47. The study showed that different colours of watermelon contributed to different antioxidant capacities and the red-fleshed watermelon had the highest antioxidant content. Furthermore, all watermelons sample could be classified as low GI food (GI value below 51) with the strong influences of component of sugar contents due to linear negative relationship between blood glucose response and glycemic index value, as well as with the amount of fructose for red-fleshed seedless, red-fleshed seeded, and yellow-fleshed watermelon.